Robot dilemmas: Deception and digital emotional labor in dementia care work - Redmalm, David; Iversen, Clara; Persson, Marcus; Thunman, Elin (Nordic Journal of Working Life Studies, 2025)
Based on in-depth interviews with care workers and observational visits to nursing homes, this study investigates how care workers address residents’ frequent misperceptions of robot cats and dogs as real animals. The analysis focuses on two aspects: how care workers handle the fact that residents often mistake the robots for real animals, and how their approach to deceptive practices relation to the robots is related to emotional labor. Three main strategies are identified and explored: telling the truth, remaining vague, and lying. While the first strategy prioritizes ethical guidelines over residents’ wellbeing in the moment, the second two strategies are facilitated by physical and verbal cues, as well as storytelling in collaboration with colleagues and residents. Each strategy also entails a dilemma, as each carries its own ethical challenges.